2019
DOI: 10.1177/2050312119840518
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care services in families of males with muscular dystrophy: Data from MD STARnet

Abstract: Introduction: Information on use of palliative care services among individuals with Duchenne and Becker muscular dystrophy is scant despite the clearly documented need. Methods: We examined associations between uptake of palliative care services by 233 males with Duchenne and Becker muscular dystrophy aged 12 and older for both caregiver and affected male characteristics using the Muscular Dystrophy Surveillance Tracking and Research Network baseline interview. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…This differs from both Edwards and colleagues, and Birnkrant and Noritz, who reported a patient‐caregiver‐perceived plateau of relative stability, which was a potential barrier to PC conversations 16,20,21 . Second, despite robust PC availability at both recruitment sites, the percentage of participants receiving pediatric PC in this cohort is dramatically lower than the 91% reported by Andrews and colleagues 14 . Taken together with results from the present study, there seems to be non‐uniform integration of PC services for patients with DMD nationally.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This differs from both Edwards and colleagues, and Birnkrant and Noritz, who reported a patient‐caregiver‐perceived plateau of relative stability, which was a potential barrier to PC conversations 16,20,21 . Second, despite robust PC availability at both recruitment sites, the percentage of participants receiving pediatric PC in this cohort is dramatically lower than the 91% reported by Andrews and colleagues 14 . Taken together with results from the present study, there seems to be non‐uniform integration of PC services for patients with DMD nationally.…”
Section: Discussioncontrasting
confidence: 84%
“…Palliative care (PC) clinicians are skilled in pain and symptom management and assessing and documenting goals of care. Andrews and colleagues reported the use of at least one PC service by 91% of 233 sampled caregiver/patient dyads seen within the Muscular Dystrophy Surveillance and Research Network (MD STARnet) sites 14 . Despite this apparent high penetration of PC services in patients with DMD, case management was the only service utilized by more than half of the participants.…”
Section: Assessment Of the Relationship Between Disease Progression A...mentioning
confidence: 99%
“…The palliative care needs of individuals with Neuromuscular Disorders will vary greatly depending on their diagnosis and goal of care [49]. Prognostication may be offered to the patient and family at the time of diagnosis and with changes in condition.…”
Section: Palliative Care In Neuromuscular Diseasementioning
confidence: 99%
“…Palliative care input can provide positive support to patients with NMD, such as the perception of control over their illness, management of troublesome symptoms and future planning [100][101][102]. Qualitative assessments of patients [103] and bereaved relatives [104] have reported that patients would welcome the input of palliative services, and that otherwise death can involve unmanaged respiratory and psychological symptoms.…”
Section: End-of-life Considerationsmentioning
confidence: 99%